EXPRESSION OF IMMUNOCORRECTIVE EFFECTS OF PHENOTROPIL AT DIFFERENT TERMS OF INDUCED IMMUNOSUPPRESSION - M. A. Samotrueva; I. N. Tyurenkov; D. L. Teplyi; S. A. Luzhnova; M. M. Magomedov (Медицинская иммунология)
Abstract. In present work, an immunocorrective effect of phenotropil after intraperitoneal injection (50 mg/kgx3) was studied in CBA mice. The drug was administered either before antigenic stimulation, and/or cyclophosphamide-induced immunosuppression, or at the terms of evolving immune deficiency. Phenotropil was shown to prevent the development of immune pathology which manifested as inhibition at all steps of immunogenesis, thus suggesting a preventive potential of its immunocorrective properties.